2009
DOI: 10.1118/1.3168556
|View full text |Cite
|
Sign up to set email alerts
|

The local enhancement of radiation dose from photons of MeV energies obtained by introducing materials of high atomic number into the treatment region

Abstract: With the advent of therapeutic radiation treatment machines with photon end point energies of several MeV, a new channel is available to transfer the photon energy to biological material, namely, pair production. This process has a photon threshold energy of 1.02 MeV. The probability of pair production, which depends on the square of the atomic number (Z) of the interacting material, increases markedly as the photon energy is further increased. As the goal of treatment planning in radiation therapy is to local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…5(c) and 5(d). Wayne D Newhauser, et al reported that the electron energy range at 500 keV in the water is approximately 2 mm 22. The electron range in the Lipiodol is shorter than the water because the Lipiodol is high density and high Z material.…”
Section: Discussionmentioning
confidence: 99%
“…5(c) and 5(d). Wayne D Newhauser, et al reported that the electron energy range at 500 keV in the water is approximately 2 mm 22. The electron range in the Lipiodol is shorter than the water because the Lipiodol is high density and high Z material.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Ahmad, etc. [11], a maximum dose enhancement of 44% using an 18 MV photon beam was observed with Au foils imbedded in the phantom.…”
Section: Introductionmentioning
confidence: 91%
“…The current study is an extension of Alkhatib et al, who studied the dose enhancement by increased electron-positronpair production of a high-Z material with high energy photon beams. 18 By using a 3D PGD technique, we measured full 3D dose distribution in the vicinity of the lead foils. The results showed, for example, that the dose enhancement between foils in the orthogonal configuration occurred at a point closer to the first foil and the range of the increased dose on the upstream side of the first foil extends much further compared to the range of increased dose on the downstream side of the second foil, which fell off rapidly.…”
Section: A Dose Enhancement In Two Foil Experimentsmentioning
confidence: 99%
“…In fact, Alkhatib et al proposed such an idea and demonstrated that there is as much as a 44% dose increase when an 18 MV photon beam is used in a water-like medium including thin gold foils. 17,18 The biological effects of the local dose enhancement near metallic materials should be carefully considered for radiation therapy of patients with an implant made of high-Z material. 19 Since more and more patients receive implants for health reasons, this will become a significant treatment-related issue in the radiation oncology community in coming years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation